Effect of the Deep Marin Balambo Formation on the Qamchuqa Reservoirs in Jambur Field - Shwani, Ayub Mohammed Ahmed; Qadir, Jayran K.; Rahman, Shukur A.; Alsaqi, Ali S. Alsaqi; Nooralddin, Amel K. (Journal of Petroleum Research and Studies, 2024)
A shallow-marine carbonate known as Qamchuqa Formation was originally discovered in northern Iraq’s Qamchuqa Gorge at an outcrop section. For the present study the available conventional well logs include gamma ray, porosity logs (density, and neutron) with the resistivity logs used to achieve the depositional environment of the studied area in selected wells Ja-21, Ja-32, Ja-41, Ja-46, and Ja-18. The Aptian-Albian age include lower and upper Qamchuqa formations, respectively are considered a major reservoir in Jambur Oil field; therefore, the present study focused only on lower and upper Qamchuqa formations. Deep marine environment Balambo Formation separated the Aptian-Albian reservoir into three parts each part is different in petrophysical properties and lithology composition. Zone -1 is shoal facies including lower and upper Qamchuqa formations composed of dolomite, dolomitic limestone and limestone, this part is far from interfingers with Balambo Formation. Zone -2 is mixed facies between shoal facies and basinal facies composed of limestone, marly limestone,shaly limestone and with a few streaks of dolomitic limestone. This part includes well Ja-32, Ja-41, and Ja-46. Zone -3 basinal facies include Balambo Formation composed of limestone, shaly and marly limestone involving well Ja-18 only. These differences above caused interfingering and lateral change in both reservoir units (lower and upper Qamchuqa formations) with Balambo Formation, and both are not depicting reservoir in Zone -2 and especially in Zone -3. The current study explains well Ja-18 located on the permanent basin and well Ja-32, Ja-41, and Ja-46 located between permanent basin and neritic zone (mixed zone or slope margin); therefore, the south east of Jambur Oil field abandoned to drill in it to Cretaceous age.